1999
DOI: 10.1007/s11894-999-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability, leaky gut, and intestinal disorders

Abstract: A major task of the intestine is to form a defensive barrier to prevent absorption of damaging substances from the external environment. This protective function of the intestinal mucosa is called permeability. Clinicians can use inert, nonmetabolized sugars such as mannitol, rhamnose, or lactulose to measure the permeability barrier or the degree of leakiness of the intestinal mucosa. Ample evidence indicates that permeability is increased in most patients with Crohn's disease and in 10% to 20% of their clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
149
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(161 citation statements)
references
References 48 publications
1
149
1
3
Order By: Relevance
“…This test is considered a reproducible, reliable, and well-established noninvasive method for assessing intestinal passive permeability, and it has been used extensively to evaluate mucosal integrity in several disease states and in healthy individuals. 13,[15][16][17]25 Sucrose was added to the lactulose/ mannitol solution as a permeability probe for absorption through the stomach and proximal duodenum. [27][28][29][30][31][32][33] Permeability tests were carried out starting at 08:00 to 09:00 AM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This test is considered a reproducible, reliable, and well-established noninvasive method for assessing intestinal passive permeability, and it has been used extensively to evaluate mucosal integrity in several disease states and in healthy individuals. 13,[15][16][17]25 Sucrose was added to the lactulose/ mannitol solution as a permeability probe for absorption through the stomach and proximal duodenum. [27][28][29][30][31][32][33] Permeability tests were carried out starting at 08:00 to 09:00 AM.…”
Section: Methodsmentioning
confidence: 99%
“…An increased intestinal permeability has been observed in patients with enteric damage, such as in inflammatory bowel disease and coeliac disease, in intestinal infections, during the intake of aspirin, nonsteroidal anti-inflammatory drugs, or alcohol, in malnourished individuals, after burns, during total parenteral nutrition, in critically ill patients, and also in various extraintestinal diseases. [5][6][7][8][9][10][11][12][13][14][15][16][17] These conditions determine a "leaky gut syndrome" with increased portal uptake of inflammatory mediators, bacteria, antigens, and toxins, enhancing the systemic distribution of potentially injurious macromolecules.…”
mentioning
confidence: 99%
“…A recent study demonstrated that GDNF has direct effects on enterocytes, especially under conditions of immature barrier functions, which are usually seen in the crypts of the intestine. In the mammalian intestinal crypt tight junction morphology is scattered (4,19) and the permeability of different tracers suggests that intestinal villi have a huge number of narrow tight junctions, whereas junctions in the crypts are more leaky (27). These observations emphasize the need to investigate cells at different stages of differentiation to fully understand the function of the IEB.…”
Section: Gdnf Directly Promotes Barrier Maturation and Proliferationmentioning
confidence: 99%
“…The molecular mechanisms that govern barrier function are incompletely understood, but it is clear that under conditions of starvation and disease, the gut barrier becomes impaired, leading to significant morbidity and mortality (1)(2)(3)(4)(5)(6)(7)(8). Trophic enteral feeding to prevent gut mucosal atrophy and resultant barrier dysfunction has become part of the standard treatment of intensive care unit patients (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%